Are Slow Streets Shared Streets? An Analysis of Communities Served by San Francisco's Slow Streets Program - Gerigk, Jacob. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Rebecca Shakespeare.; Committee: Sumeeta Srinivasan.; Keywords: Urban planning, and Transportation.